2014
DOI: 10.1007/s00264-014-2352-8
|View full text |Cite
|
Sign up to set email alerts
|

New preclinical porcine model of femoral head osteonecrosis to test mesenchymal stromal cell efficiency in regenerative medicine

Abstract: Cryoinjury associated with partial vascular coagulation is sufficient to obtain localised and sustainable necrosis in the subchondral area of the femoral head, reproducing all stages of the human disorder. The co-analysis by MRI and histology allowed us to confirm that the classic T1- and T2-weighted hyposignal regeneration front around a fatty high T1-weighted signal observed by MRI indicate signs of induced osteonecrosis. Our results indicate that our pig model induces all stages of human ONFH, which can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…However, nONFH is rare in pigs. To have a statistically relevant result of the effectiveness of BMSCs on this painful disease, it is necessary to test this approach on one of the models of ONFH which has been developed in either emu or pig and to conduct a study on a large number of animals [ 26 , 44 ]. As the effectiveness of BMSCs has been proven and we and others showed the safety of this approach, the second strategy could be to go directly to the clinic [ 6 , 7 , 13 , 14 , 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nONFH is rare in pigs. To have a statistically relevant result of the effectiveness of BMSCs on this painful disease, it is necessary to test this approach on one of the models of ONFH which has been developed in either emu or pig and to conduct a study on a large number of animals [ 26 , 44 ]. As the effectiveness of BMSCs has been proven and we and others showed the safety of this approach, the second strategy could be to go directly to the clinic [ 6 , 7 , 13 , 14 , 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pigs were managed in accordance with the instructions of the ethics committee. Access to FH was done in accordance with the previously described protocol by a percutaneous approach of the hip [ 26 ]. Pigs received an injection of 140 × 10 6 autologous pBMSCs (n = 1) or hBMSCs (n = 2) in 7 mL of 5% human serum albumin (Albunorm; Octapharma, Boulogne-Billancourt, France), and one pig served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Drescher et al [79] treated pigs with corticosteroids and observed contraction of femoral head lateral epiphyseal arteries in treated animals, but noted no evidence of ONFH in these pigs. In another report by Poignard et al [80], 18 female pigs were used to creat ONFH by cryo-injury, the authors noted localized and sustainable subchondral necrosis of the femoral head, reproducing all stages of the human disease. Moreover, the good correlation between histological and MRI results indicates that the pig is a relevant model for human ONFH.…”
Section: Other Animal Modelsmentioning
confidence: 95%
“…Non-cellular therapeutic strategies using growth factors have been proposed; however, there has been little progress with regard to the verification of animal experiments, primarily because of the absence of an animal model for femoral head-specific necrosis [9,16] and secondarily because of the lack of a technique to locally deliver the growth factor [17]. The angiogenic and osteogenic actions of rhFGF-2 have been the subject of numerous reports for bone and joint disease.…”
Section: Discussionmentioning
confidence: 99%